The Jewish Bible : A Material History - Stern, David, 1949- (Book collections on Project MUSE., 2017)
"In The Jewish Bible: A Material History, David Stern explores the Jewish Bible as a material object--the Bibles that Jews have actually held in their hands--from its beginnings in the ancient Near Eastern world through to the Middle Ages to the present moment. Drawing on the most recent scholarship on the history of the book, Stern shows how the Bible has been not only a medium for transmitting its text--the word of God--but a physical object with a meaning of its own. That meaning has changed, as the material shape of the Bible has changed, from scroll to codex, and from manuscript to printed book. By tracing the material form of the Torah, Stern demonstrates how the process of these transformations echo the cultural, political, intellectual, religious, and geographic changes of the Jewish community. With tremendous historical range and breadth, this book offers a fresh approach to understanding the Bible's place and significance in Jewish culture"--